The role of nutrition and gut microbiome in the progression of multiple myeloma and its precursor disease - Kanellos, Panagiotis T.; Baxevanis, Georgios K.; Tentolouris, Anastasios; Gavriatopoulou, Maria; Ntanasis-Stathopoulos, Ioannis (Frontiers in Oncology, 2024)
Multiple myeloma (MM) is the second most common hematological malignancy, characterized by unregulated monoclonal proliferation in the bone marrow. Monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM) are premalignant conditions that can progress to MM. Identifying etiological risk factors for MM and its precursor diseases is crucial for prevention. Obesity, diet, vitamin D levels, and gut microbiota alterations have been identified as lifestyle factors affecting MM and MGUS risk. Upon disease onset, treatment strategies aim to reduce disease burden, enhance prognosis, and optimize patients’ quality of life. Nutrition and body weight have been shown to affect disease progression and treatment outcomes. MM patients often present with vitamin D, vitamin B12, and folate deficiencies, which worsen disease prognosis. High body mass index is linked to increased death rates among MM patients and an increased risk of MGUS transformation to MM. Gut microbiota has also been associated with disease progression and response to treatment. This literature review aims to summarize the available evidence regarding the impact of nutrition and nutritional status on MM patients beyond prevention, highlighting the significance of gut microbiome and dysbiosis in MM progression.